The emerald tide - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay, 2022)
Still mourning his wife four years after her death, art history teacher and auction house consultant Derek Gaines teams up with Kelly Reid, the head of gallery operations at Christie's Los Angeles, to track down a stolen painting.